Corporate environmentalism: an assessment of sustainability reporting among firms in Ghana. (28th June 2019) - Ahenkan, Albert; Aboagye, Alice Anima; Boon, Emmanuel Kwesi
This article argues that corporate environmentalism and sustainability reporting are key instruments for achieving socio-economic progress in Ghana and the goals of the United Nations post 2030 Development Agenda. To support this argument, the level and quality of sustainability reporting by firms listed on the Ghana Stock Exchange are critically examined. Using purposive and convenience sampling techniques, 13 of these companies were selected and investigated on their engagement in sustainability reporting using the global reporting initiative (GRI) framework. Data and information gleaned from the annual reports of the sampled firms were studied and subjected to content analysis with the help of GRI G4 reporting analytical benchmark. The results indicate that the quality of sustainability reporting is low though a few of the disclosures made by the firms met the GRI framework requirements. It is recommended that sustainability reporting by firms in Ghana should be made mandatory and not voluntary.